"SEBAMBANGAN" TRADITION: LOCAL WISDOM OF THE SAIBATIN INDIGENOUS MARRIAGE IN LAMPUNG - Suwarjin Suwarjin (JURNAL ILMIAH MIZANI: Wacana Hukum, Ekonomi, dan Keagamaan, 2021)
"Sebambangan" marriage is a custom in which the male party will run away the girl brought to the male's family to reduce conflict between the parties or relatives directly involved in the implementation of the marriage due to differences in social and economic status. This marriage raises pros and cons among the indigenous people of Lampung's Saibatin. This research examines this "sebambangan" customary local wisdom from the perspective of local wisdom in Islamic law (urf). The research method used is qualitative field research with a normative-sociological approach. The results of the study found that the Sebambangan custom, namely bachelors carrying girls away, was based on the agreement of both parties. The factor of the Sebambangan customary marriage is that the terms of payment, financing and the marriage ceremony requested by the girl cannot be fulfilled by the bachelor; one of the girl's older sisters is not married and vice versa. When viewed from the 'Urf, the Sebambangan Adat is 'urf authentic, but in practice, there is a fasid 'urf, which is related to the factor of the existence of the Sebambangan customary marriage, one of which is: honest money is too high which is not under the values in Shari'a at Islam. Pernikahan “Sebambangan” adalah suatu adat di mana pihak laki-laki akan melarikan gadis yang dibawa ketempat keluarga laki-laki untuk mengurangi konflik di antara para pihak atau kerabat yang terlibat langsung dalam pelaksanaan perkawinan akibat perbedaan status sosial dan ekonomi. Pernikahan ini menimbulkan pro dan kontra di kalangan masyarakat adat saibatin lampung. Penelitian ini mengkaji kearifan lokal adat “sebambangan” ini dalam perspektif kearifan lokal dalam hukum Islam (urf). Metode penelitian yang digunakan adalah penelitian kualitatif lapangan dengan pendekatan normatif-sosiologis. Hasil penelitian menemukan bahwa adat Sebambangan yaitu bujang membawa lari gadis yang berdasarkan kesepakatan kedua pihak. faktor perkawinan Adat Sebambangan adalah syarat-syarat pembayaran, pembiayaan dan upacara perkawinan yang diminta pihak gadis tidak dapat dipenuhi pihak bujang, salah satu kakak perempuan si gadis ada yang belum menikah dan begitu juga sebaliknya. Jika dilihat dari ‘Urf, maka Adat Sebambangan merupakan ‘urf shahih, namun dalam praktiknya terdapat ‘urf yang fasid, yaitu yang berkaitan dengan faktor adanya perkawinan adat Sebambangan yang salah satunya yaitu: uang jujur terlalu tinggi yang tidak sesuai dengan nilai-nilai dalam syari’at Islam.